Exploration and evaluation of a system for interactive sonification of elite rowing - Dubus, G.; Bresin, R. (Sports Engineering, 2015)
In recent years, many solutions based on interactive sonification have been introduced for enhancing sport training. Few of them have been assessed in terms of efficiency or design. In a previous study, we performed a quantitative evaluation of four models for the sonification of elite rowing in a non-interactive context. For the present article, we conducted on-water experiments to investigate the effects of some of these models on two kinematic quantities: stroke rate value and fluctuations in boat velocity. To this end, elite rowers interacted with discrete and continuous auditory displays in two experiments. A method for computing an average rowing cycle is introduced, together with a measure of velocity fluctuations. Participants answered to questionnaires and interviews to assess the degree of acceptance of the different models and to reveal common trends and individual preferences. No significant effect of sonification could be determined in either of the two experiments. The measure of velocity fluctuations was found to depend linearly on stroke rate. Participants provided feedback about their aesthetic preferences and functional needs during interviews, allowing us to improve the models for future experiments to be conducted over longer periods.